CAS 2010 Proceedings (International Semiconductor Conference) 2010
DOI: 10.1109/smicnd.2010.5649077
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the gas sensing properties readout with n and p-type MOX materials

Abstract: The way in which surface changes are transduced into a variation of an electrical parameter (often electrical resistance) depends on the surface oxidation level, material morphology its semiconductor behaviour, etc. Therefore, if one wants to understand more about the way in which gassurface interactions affect the gas sensing properties of material, complex phenomenological and spectroscopic investigations are needed. Herein, by simultaneous DC and relative work function investigations we could explain the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…However, contrary to this, both the hybrid structures in our study showed p-type behaviour. This observed inconsistency is due to the increase in barrier height of approximately 2.90 meV for the ZnO-NR and 2.10 meV for the ZnO-TF hybrid structure (measured from the work function equation), thus contributing to the overall increase in resistance [ 76 ]. One of the possible explanations can be the dipole–dipole interactions between the extracellular site of the protein and ethanol molecules, which leads to the electron transfer between the surface and the interior layer [ 77 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, contrary to this, both the hybrid structures in our study showed p-type behaviour. This observed inconsistency is due to the increase in barrier height of approximately 2.90 meV for the ZnO-NR and 2.10 meV for the ZnO-TF hybrid structure (measured from the work function equation), thus contributing to the overall increase in resistance [ 76 ]. One of the possible explanations can be the dipole–dipole interactions between the extracellular site of the protein and ethanol molecules, which leads to the electron transfer between the surface and the interior layer [ 77 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shape [15] and, more importantly, the dimensions [16] of the nanostructures influence the sensing performance of the sensors; therefore, one of the most used materials are nanowires (NWs). N-type semiconductors have been studied for longer and more thoroughly as they perform better as gas detectors [17,18]. The two materials most studied previously are SnO 2 and ZnO, which are still the most used owing to their superior performance.…”
Section: Introductionmentioning
confidence: 99%